1855 Ky. Acts 96 - (:unkn) unknown (My University, 1855)
Ch. 636: Prohibited vending, buying, selling, or dealing in colts, brass knuckles, slung-shots, or any imitation or substitute therefor. Violators fined twenty-five dollars. Any use of the above to strike, beat, wound, or bruise another shall be punished by forfeit of the weapon and a fine of one hundred dollars to go to the victim.
Keywords: COMMITTING CRIME W/ WEAPON; TRANSFER